PENGEMBANGAN MEDIA PEMBELAJARAN TRAINER MIKROKONTROLER PADA JURURSAN TEKNIK ELEKTRONIKA SMK NEGERI DI MAKASSAR - Akmaluddin; Hasanah Nur; Darlan Sidik (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2022)
This research aims to; (1)knowing the stages in developing a microcontroller trainer learning media.; (2)produce a valid and practical Microcontroller trainer learning media used in SMK; (3) produce a Microcontroller trainer learning media that is effective in improving student learning outcomes in SMK. This research method is Research and Development with a 4D development model. The research subjects were 25 students of State Vocational High School in Makassar City, majoring in electronics engineering. Data collection through documentation, observation and questionnaire methods were analyzed using quantitative descriptive statistical techniques. The results of the research on developing learning media based on smartphone application modules through the following stages: (1) analyzing the need for developing learning media and the feasibility and requirements for developing a microcontroller-based media trainer.Alf and Vegard RISC (AVR); (2) the design stage of designing learning devices and media; (3) development by looking at the responses of validators/experts from the designs that have been made, namely the feasibility of the media and the feasibility of the material as well as the feasibility of instruments and questions for students/students; (4) the distribution is carried out in 2 stages of activity, namely the Pre-Test stage which is used as initial data and the Post-Test stage and the implementation stage which is used as the final data to see the comparison and percentage of product success made. The quality of the learning media was declared very valid by the media expert validator with a value of 99% and material expert with a value of 99%. The practicality of the media based on student questionnaires from the one to one test got a score of 88%, the small group test 92% and the large group test 90% were in the very practical category. Effectiveness is stated based on the results of the pretest and posttest. The data obtained shows N-Gainof 0.81 which is in the high category where the average value of students before use is 55.37 and increased to 81.05after using the microcontroller media trainer, The increase in the value can be concluded that the microcontroller trainer media has been effective in its use.